2022
DOI: 10.4103/jewd.jewd_67_21
|View full text |Cite
|
Sign up to set email alerts
|

Onychomycosis in chronic liver disease

Eman Adel Elmansoury,
Adel Ali Ebrahim,
Talaat Abdelrazek Othman
et al.

Abstract: Background Nail changes including onychomycosis are clues to many systemic diseases. The prevalence of this disease is variable worldwide and in different patient groups. Objective To study the prevalence of onychomycosis among chronic liver disease (CLD) patients, the association of risk factors in that patient category with onychomycosis, the causative fungal species, and antifungal susceptibility of the most common species isolated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…37 In HIV-positive individuals, most patients who developed onychomycosis presented with the distal lateral subungual pattern and an average CD 4 count of 370/μL. 38 Despite a previous systematic review demonstrating a potential relative increase in the prevalence of pediatric onychomycosis, 118 our results indicate that the risk of onychomycosis is significantly lower in children (RR: 0.1) possibility due to faster nail growth, good peripheral circulation and less likelihood of nail trauma. Since the latest study we identified that reported on pediatric onychomycosis was published in 2016, 23 newer studies may be warranted to confirm this trend.…”
mentioning
confidence: 58%
See 2 more Smart Citations
“…37 In HIV-positive individuals, most patients who developed onychomycosis presented with the distal lateral subungual pattern and an average CD 4 count of 370/μL. 38 Despite a previous systematic review demonstrating a potential relative increase in the prevalence of pediatric onychomycosis, 118 our results indicate that the risk of onychomycosis is significantly lower in children (RR: 0.1) possibility due to faster nail growth, good peripheral circulation and less likelihood of nail trauma. Since the latest study we identified that reported on pediatric onychomycosis was published in 2016, 23 newer studies may be warranted to confirm this trend.…”
mentioning
confidence: 58%
“…Sufficient data were available from clinically un‐suspected patients to determine the risks of onychomycosis in special populations relative to the general population 11,18,20,22,23,27,28,31–45 . A significantly higher risk ( p < .05) was found in the following special populations (Figure 2) (in decreasing order): knee osteoarthritis patients (RR: 14.6 [95% CI: 13.0–16.5]), chronic venous disease patients (RR: 5.6 [95% CI: 3.7–8.1]), kidney transplant patients (RR: 4.7 [95% CI: 3.3–6.5]), geriatric patients (RR: 4.7 [95% CI: 4.4–4.9]), HIV‐positive patients (RR: 3.7 [95% CI: 2.9–4.7]), lupus erythematosus patients (RR: 3.1 [95% CI: 1.2–6.3]), diabetic patients (RR: 2.8 [95% CI: 2.4–3.3]), hemodialysis patients (RR: 2.8 [95% CI: 1.9–4.0]) and psoriasis patients (RR: 1.6 [95% CI: 1.2–2.1]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation